Multiple FAS1 domains and the RGD motif of TGFBI act cooperatively to bind alpha v beta 3 integrin, leading to anti-angiogenic and anti-tumor effects - Son, Hye-Nam; Nam, Ju-Ock; Kim, Soyoun; Kim, In San (ELSEVIER SCIENCE BV, 2013)
TGFBI, a transforming growth factor beta-induced extracellular matrix protein, circulates at a level of similar to 300 ng/ml in humans and modulates several integrin-mediated cellular functions. The protein contains an N-terminal EMI domain, four consecutive FAS1 domains, and the RGD motif. Each FAS1 domain and the RGD motif have been known to interact with avb3 integrin. Here, we found that the binding affinity (K-d) of TGFBI for alpha v beta 3 integrin was approximately 3.8 x 10(-8) M, a value similar to 2300-fold higher than that of a single FAS1 domain, and demonstrated that this greater affinity was due to the cooperative action of the four FAS1 domains and the RGD motif. Moreover, TGFBI exhibited more potent anti-angiogenic and anti-tumorigenic activities, even at a 100-fold lower molar dose than the reported effective dose of the FAS1 domain. Finally, our data showed that TGFBI specifically targeted the tumor vasculature and accumulated at the tumor site. Collectively, our results support the theory that TGFBI acts as a potent endogenous anti-tumor and anti-angiogenic molecule by targeting alpha v beta 3 integrin, and highlights the importance of physiological circulating TGFBI levels in inhibiting tumor growth. (C) 2013 Elsevier B.V. All rights reserved.